THE INFLUENCE OF POPULISM ON THE DEVELOPMENT OF NON-STATE ACTORS IN THE EUROPEAN UNION - Jarosław Filip Czub (Srpska Politička Misao)
The article assesses the impact of populism on the functioning of non-state actors in the European Union.The main aim of this paper is to verify whether populism has had an impact on the functioning of non-state actors in the European Union. The article focuses onthe non-state actors involved in European and country-level lobbying. The article also attempts to determine the place of non-state actors within the institutional system of the European Union in the context of the rise of populism in European Member States. In addition to its theoretical dimensions, the paper offers a practical approach to the functioning of non-state actors against the backdrop of populism, which has been developing in recent years in the European Union. This rising populism has had a significant impact on sectoral and non-sectoral non-state actors in eachof the member states of the European Union.